GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 41698 species occurrences available in GBIF matching the query: Country: Spain TaxonKey: Genista eliassennenii Uribe-Ech. & Urrutia or Himantoglossum hircinum var. hircinum or Huperzia selago (L.) Bernh. ex Schrank & Mart. or Juncus acutus L. or Littorella uniflora Asch. or Lomelosia graminifolia (L.) Greuter & Burdet or Luzula nutans (Vill.) Duval-Jouve or Nepeta tuberosa L. or Ophioglossum vulgatum L. or Paris quadrifolia L. or Pedicularis foliosa L. or Petrocoptis pyrenaica A.Braun ex Walp. or Pinguicula lusitanica L. or Pulsatilla alpina subsp. cantabrica M.Laínz or Radiola linoides Roth or Salix aurita L. or Salix cantabrica Rech.f. or Sempervivum vicentei Pau or Stachys palustris L. or Suaeda maritima (L.) Dumort. or Viola bubanii Timb. or Buxus sempervirens L. or Convolvulus lineatus L. or Narcissus asturiensis (Jord.) Pugsley or Narcissus bulbocodium L.. The dataset includes 41698 records from 98 constituent datasets: 2 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 5 records from Phanerogamic Botanical Collections (S). 4 records from University of Vienna, Institute for Botany - Herbarium WU. 131 records from Naturalis Biodiversity Center (NL) - Botany. 306 records from SANT herbarium vascular plants collection. 5 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 13 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Tallinn Botanic Garden. 8 records from Herbarium areqvipense (HUSA). 7417 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 24 records from Banco de Germoplasma del Jardín Botánico Atlántico. 3 records from iNaturalist Research-grade Observations. 1 records from UCBG TAPIR Provider. 2 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 10 records from NMNH occurrence DwC-A. 2 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 68 records from Herbario de la Universidad de Granada: GDA. 135 records from naturgucker. 1 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 1 records from BioBlitz Barcelona 2010-14. 493 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 8 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 25 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 2 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 1 records from Tropicos Specimen Data. 14 records from Natural History Museum (London) Collection Specimens. 762 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 10 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 42 records from Natural History Museum, Vienna - Herbarium W. 51 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 1 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 23 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 492 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 552 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 1509 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 34 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 30 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 20 records from Herbario de la Universidad de Almeria. 261 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 112 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 84 records from Jardín Botánico de Córdoba: Herbarium COA. 242 records from Aranzadi Zientzi Elkartea. 17 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 17 records from Universitat de Girona: HGI-Cormophyta. 75 records from CIBIO, Alicante:ABH-GBIF. 1 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 94 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 49 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 530 records from Herbario de la Universidad de Sevilla. 23 records from Herbario de la Universidad de Sevilla, SEV-Historico. 211 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 92 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 118 records from Institut Botanic de Barcelona, BC. 15 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 5 records from Herbarium Berolinense. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 4 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 7 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 37 records from Institut Botanic de Barcelona, BC-Histórico. 7 records from EURISCO, The European Genetic Resources Search Catalogue. 1522 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1747 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 47 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 118 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 19 records from Jardín Botánico Atlántico, Gijón: JBAG. 150 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 1 records from Biological and palaeontological collection and observation data MNHNL. 2 records from Herbarium Senckenbergianum (FR). 224 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 32 records from Herbario de Universidad de Murcia: MUB. 905 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 9016 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 4 records from Lund Botanical Museum (LD). 5 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Carnet en Ligne. 1 records from Herbario IES San Isidoro de Sevilla. 10 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 5 records from Royal Botanic Garden Edinburgh Herbarium (E). 4 records from Botany (UPS). 11 records from Museu de Ciències Naturals de Barcelona: BGJBB. 6 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 30 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 9215 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 81 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 24 records from Vascular Plant Herbarium, Oslo (O). 1 records from The Bergius Herbarium. 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 2 records from Anymals+plants - Citizen Science Data. 48 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 1 records from SysTax - Herbaria. 6 records from Geneva Herbarium – General Collection (G). 1 records from BoGART. 4228 records from Tercer Inventario Forestal Nacional. Ministerio de Agricultura, Alimentación y Medio Ambiente (España/Spain). 11 records from Dataset of Phenology of flora of mediterranean high-mountains meadows (Sierra Nevada).
Keywords: GBIF; biodiversity; species occurrences